Malaria In Symptomatic Patients Attending A Federal Medical Centre In Central Nigeria (FULAFIA IAC Book of Proceedings, 2024)
Malaria remains an ongoing problem in Nigeria even though a lot has been achieved in the past years; millions of people are still at risk of contracting the parasite. Thus, this study determined the malaria prevalence in symptomatic patients attending a Federal Medical Centre in Central Nigeria. Five milliliters (5mls) of blood was collected from 250 patients between July and December 2023 by the use of a well labeled ethylene diamine tetraacetic acid (EDTA) vacutainer tube and malaria parasite test was conducted using microscopy and Rapid Diagnostic Test (RDT). Out of a total of 250 patients examined for malaria parasite in this study, 132 (52.8%) were significantly (P
Keywords: Keffi; Malaria; Parasites; Symptomatic patients